“Kuchoka”: Investigation of research fatigue in Mosoriot, Kenya - Felishana Cherop; Violet Naanyu; Juddy Wachira; Lukoye Atwoli (PLoS ONE, 2026)
Background Health research is key to the promotion of population and community health, however, conducting many research studies in a community can cause research fatigue. Purpose We determined the prevalence of research fatigue and associated factors in Mosoriot, Kenya. Methods We conducted a cross-sectional study in the Mosoriot community from Wednesday 28, May 2014, to Thursday 30, April 2015, involving (n = 327) community members who were randomly sampled to respond to self-administered and/or guided questionnaires. We analyzed descriptive statistics to summarise the data and used the Pearson Chi-Square test to assess the bivariate associations between the variables and conducted multivariate analyses using logistic regression models to test the hypotheses. The odds ratios and the corresponding 95% confidence limits were reported. Results Research fatigue prevalence was 56.3% and the factors associated included being >35 years (OR: 2.28, 95% CL: 1.27, 4.15), being male (OR: 2.80, 95% CL:1.59, 5.00), self-employment (OR: 2.05, 95% CL: 1.06, 4.01), participating in hospital-based studies (OR: 3.59, 95% CL:1.88, 7.09), involvement in multiple researches (OR: 3.86, 95% CL:1.87, 8.27), desire to drop out of a study (OR: 11.49, 95% CL: 3.69, 43.83) and being asked personal questions (OR: 6.23, 95% CL: 3.28, 12.23). Conclusion There is a high prevalence of research fatigue (56.3%) among community members in Mosoriot who have participated in repeated research, which is associated with age, gender, income source, research setting, frequency of research engagement, desire to drop out of studies, and discomfort with questions. Addressing research fatigue would enhance ethical research conduct and promote sustained community participation in research.